The relationship between shifts in the rhizosphere microbial community and root rot disease in a continuous cropping American ginseng system - Bi, Yan-Meng; Zhang, Xi-Mei; Jiao, Xiao-Lin; Li, Jun-Fei; Peng, Na; Tian, Gei-Lin; Wang, Yi; Gao, Wei-Wei (Frontiers in Microbiology, 2023)
The root rot disease causes a great economic loss and the disease severity is usually increased with ginseng ages. However, whether the disease severity is related with changes of microorganisms during the whole growing stage of American ginseng was still unclear. In the present study, the rhizosphere microbial community and soil chemical properties of 1 to 4 years’ old ginseng of different growing seasons in two sites were characterized and the root rot disease index (DI) of ginseng was investigated. Results showed that the DI of ginseng was increased 2.2 times in one sampling site or 4.7 times in another during four years. With respect to microbial community, the bacterial diversity increased with the seasons in the first, third and fourth year but keep steady in the second year. The seasonal changing of relative abundances of bacterial and fungi taxes exhibited the same trend in the first, third and fourth year but for the second year. Linear models revealed that the relative abundances of Blastococcus, Symbiobacterium, Goffeauzyma, Entoloma, Staphylotrichum, Gymnomyces, Hirsutella, Penicillium and Suillus spp. were negatively correlated with DI, while that of Pandoraea, Rhizomicrobium, Hebeloma, Elaphomyces, Pseudeurotium, Fusarium, Geomyces, Polyscytalum, Remersonia, Rhizopus, Acremonium, Paraphaeosphaeria, Mortierella, and Metarhizium spp. were positively correlated with DI (P＜0.05). The mantel test showed that soil chemical properties, including available nitrogen, phosphorus, potassium, calcium, magnesium, organic matter and pH were significantly correlated to microbial composition. The contents of available potassium and nitrogen were positively correlated with DI, while pH and organic matter were negatively correlated with DI. In summary, we can deduce that the second year is the key period for the shift of American ginseng rhizosphere microbial community. Disease aggravation after the third year is related to deterioration of rhizosphere microecosystem.